Perbandingan Hasil Belajar Peserta Didik Kelas X SMA Negeri 1 Segeri Antara yang Diajar dengan Model Pembelajaran Kooperatif Tipe NHT dan Tipe STAD (Studi Pada Materi Pokok Ikatan Kimia) - Rezky Kurniah Syam; Muhammad Anwar; Diana Eka Pratiwi (ChemEdu, 2021)
This research is a quasi-experimental research which aims to know the difference of learning outcomes between the students that learned by using cooperative learning model with type of NHT and the students that learned by using cooperative learning model with type of STAD. The research design was “Posttest-Only Design”. The independent variables of this research are cooperative learning model with type of NHT and cooperative learning model with type of STAD, and the dependent variable is learning outcomes. The population of this research is all first grade students of SMA Negeri 1 Segeri that consist of seven classes with the number 210 students, whereas the research samples are class XH as the first experiment class and class XB as the second experiment class. Each class consists of 30 students. Data of learning outcomes is performed by givingposttest. Data that with multiple choice as much 20 items is analyzed by using descriptive statistics and inferential. The result of analysis shows that the average value of learning outcomes of the first experiment class in the posttest is 77. 16 and the second experiment class is 70.66. The result of hypothesis testing using t-testing isobtained the value as t count = 3.3859 and in the significant level of α = 0.05 with dk = 58 obtained value as t table = 1. 672. Therefore, t count>t table , so that H1 is accepted and H0 is rejected. It means that the learning outcomes of students that learned by using learning cooperative model with type of NHT is better than the students that learned by using learning cooperative model with type of STAD in the fisrt grade class of SMA Negeri 1 Segeri in the main subject of chemical bond.